Buitenlandse activiteiten van de KNOB in historisch perspectief (Bulletin KNOB, 1990)
The hereafter following is abstract of the discourse held by Prof. dr. ir. C. L. Temminck Groll in honour of the jubilee 1899-1989 of the KNOB on September 23th 1989. The KNOB (Royal Antiquarian Society of the Netherlands) exists 90 years. A respectable age after human standards. Although a society depends on human devotion it does not know age limitations.This is an excellent moment to reflect upon our centenary. Then, in 1999, we will have to present an extremely good manifest for the coming millennium! We have been spoiled very much during the past 90 years. Which of the founders would have expected so many people professionally involved at the protection of monuments? Which of them could have estimated the money available to realize restoration activities? Still, despite of all we obtained, we are rightly concerned about our country and especially that part of the world beyond our borders. These concerns are formulated by the National Geographic Society which hereby stated: 'Can we save this fragile earth?'This society aims at the earth herself as well as at human achievements. Co-operation between the protection of nature and the protection of monuments certainly is sensible and could be one of our future actions. How much nature, how much culture is not already 'dead'! Wren's St. Benet in London f.e. seems saved, but surrounded by flowing thoroughfares the church misses every relation with the original urban structure. Thus in fact the monument has not been saved. At Liège, Belgium, 20th century traffic and concrete buildings overran the medieval Place St. Lambert. And what about the European countryside? How much harmonious farmer's land has not been industrialized yet? Old structures disappear everywhere.Instead of the newly made our Society had to study more and more the continuous changes of the already extant. As to our foreign activities, we can distinguish three angles of incidence. First of all: what can we learn from other countries? Our founder mr. dr. J.C. Overvoorde already realized the importance of study of the way monuments are protected in different European countries. ICOMOS at present is the platform to discuss organizational and substantial aspects. Second: stock-taking of Dutch cultural influences to other regions in Europe, which subject used to attract more attention than it does now. At last: Dutch influences beyond European borders. Like our founder in 1910-11 studied Hindu-Buddhistic antiquaries and the monuments of the Dutch East-Indian Company our Foundation Social History of the Dutch Oversea studies these treasures now. One of her working-groups tries to solve Indonesian problems with respect to the protection of monuments and started stocktaking of especially younger architecture and town-planning.Still, a lot remains to be done on this field in the 'West'! Borders fade. But with the introduction of new fields of work we may not forget the old. Not the older monuments, since we are occupied with the young, not the Dutch, being directed at the whole world. After the question of what we study, the question rises how. Our purpose always was protection. Unlike nature culture cannot renew herself: we have to 'maintain'. And then mankind also is a piece of nature with continuous new desires to which the extant has been adapted.'Maintain' as well as 'adapt to' means: to change. We can let nature change the made - how beautifully weathered the ruins are! - but we can also preserve the weathering - until now. Replacement of weathered material by new in the shape of colour it used to have is another possibility. Also opinions about this sort of alterations are constantly changing. Thus a platform like the KNOB at national level or ICOMOS at international level will always be needed. That's why: an extremely good manifesto in 10 years. One that states that we are occupied with changing instead of static affairs. Alterations must be directed professionally in a careful and modest way. For the real is infinitely more valuable than the copy.